Peningkatan Inovasi dan Kreativitas Siswa dalam Pemanfaataan Sedotan Plastik dan Pembuatan Sabun Cuci Tangan di SDN Sumber 1 Surakarta - Utami, Indah Wahyu; Hutapea, Henny Parida; Gimnastiar , Muhamad Ramdan; Saputri, Lisa Nur Savira Dewi (Indra Institute Research & Publication, 2024)
The Merdeka Curriculum has been implemented in the Education unit. The Merdeka Curriculum consists of intracurricular activities and projects to strengthen the profile of Pancasila students. The project to strengthen the profile of Pancasila students is a supporter of intracurricular activities in the independent curriculum. This community service aims to increase the understanding of teachers and students at SDN Sumber 1 regarding the Design of Strengthening the Pancasila Student Profile Project. This activity was carried out in 3 stages, namely the preparation, implementation and monitoring evaluation stages. The results of this activity are increasing student motivation, innovation and creativity, packaged in activities involving the use of plastic straws to make crafts and training in making hand washing soap as assistance in designing a project to strengthen the profile of Pancasila students which is going well. Participants seemed enthusiastic in taking part in activities which were expected to bring innovation and creativity in making a potential product. Activity participants also carried out the practice of the project to strengthen the profile of Pancasila students independently according to what had been trained so that it could be said that the understanding of teachers and students related to the project to strengthen the profile of Pancasila students increased. One form of P5 activity for students can be the use of plastic straw waste into crafts. Plastic straws are a raw material that is very commonly used in various products, such as food and drink packaging. However, the use of plastic straws can also be an environmental problem if they are not processed properly. Another form of P5 activity for SDN Sumber 1 Surakarta schools can be making hand washing soap. The importance of using soap that is safe to use needs to be applied to schools.